Effective English Teaching for Young Learners Classrooms - Syafryadin, Syafryadin (Yavana Bhasha : Journal of English Language Education, 2020)
Being a good teacher is a challenging thing. There are a lot of responsibilities that should be taken into account. The professional teacher requires continuous development; therefore, how to teach effectively so that the students can reach maximum learning achievement should be put as the highest priority for the teachers. However, it is assumed that it is not all teachers hold the principle. Some teachers just do the teaching as their routine or their job without any effort for developing their professionalism. It was discovered that most of English language teachers in Asia use grammatical-translation method as his or her teaching method (Paul, 2003). The teachers seemingly do not care much about the purpose of language learning itself and there is no real interaction in the classroom. It is assumed that the definition of a good teacher itself is still not clear and internalized well enough by the teacher since it seems every teacher has his or her own believes and perspectives to define what they are all about. There are many terms that tell what a good teacher is e.g. ‘the successful teacher’, the teacher I like best’, ‘the teacher I learn most from’, and the like. Each of the terms delivers different meanings and tastes. In a more formal setting, simply, it can be argued that be a good teacher means be a good facilitator in the classroom, who plans, organizes, manages the instruction that is based on students’ needs and characteristics so that the students can reach maximum learning achievement. In brief, this conceptual paper intended to identify effective teaching is weighed in the English classroom for young learners.